The Evaluation of Science Learning Program, Technology and Society Application of Audio Bio Harmonic System with Solar Energy to Improve Crop Productivity (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2017)
One of the greatest challenges in science learning is how to integrate a wide range of basic scientific concepts of physics, chemistry, and biology into an integrated learning material. Research-based teaching material in this area is still very poor and does not much involve students of science education in its implementation as part of the learning program science technology and society (STS). The purpose of this study is to get the result of evaluation of the teaching and learning of STS in the form of public service in Kulon Progo, Yogyakarta. The program to improve crop productivity through the application of Audio Bio Harmonic System (ABHS) with solar energy have been selected for utilizing the natural animal sounds to open stomata of the leaves conducted during foliar fertilization, making it suitable for integrated science lessons. Component of evaluation model used is Stufflebeam model evaluation (CIPP). CIPP evaluation in these activities resulted in two aspects: The first aspect was improving the skills of students and farmers in using ABHS, and these two aspects, namely food crop productivity; (1) cayenne increased 76.4%, (2) increased red onions (56.3%) and (3) of maize increased by 67.8%. Besides, it was also the effect of the application of ABHS on the rate of plant growth. The outcome of this study is the STS teaching materials and appropriate technology of ABHS with solar energy.